PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. MINANGA GROUP PABRIK SEII ENAI MILL (SENM) - Wulanda, Nourma; Sari, Palupi Indah; Krisdayanti, Miranda (Ekonomika, 2024)
This study aimed to determine the influence of organizational culture and motivation on employees' performance at PT. Minanga Group Factory Seii Enai Mill (SENM). The data collection technique used in this study was through distributing questionnaires. Total population was 68 employees of PT. Minanga Group Factory Seii Enai Mill (SENM). The data analysis technique used was multiple linear regression. Based on the results of hypothesis testing showed that partially or t test there was an influence of organizational culture on employees' performance at PT. Minanga Group Factory Seii Enai Mill (SENM) with a tcount of (8.657) and ttable (1.99714). Thus it could be concluded that Ho was rejected and Ha was accepted. In the motivational variable there was a motivational influence on the performance of employees at PT. Minanga Group with a tcountof (5.545) and ttable (1.99714). Thus it could be concluded that Ho was rejected and Ha was accepted. The results of the study found that Fcount was 197,062. These results were then compared with F tables, F tables were obtained bylooking at (df1= number ofvariables–1) =3-1=2 and (df2=n-k-1)= 68-2-1=65 at a 95% confidence level or α = 5% obtained Ftable 3.14. So Fcount 197.062 > Ftable 3.14 then Ho was rejected and Ha was accepted, meaning that simultaneously there was a significant influence of organizational culture and motivation on the performance of employees of PT. Minanga Group Factory Seii Enai Mill (SENM).The coefficient of determination (R2) obtained was0.858. This showed that the contribution of the influence of organizational culture and motivation on employees' performance was 85.8% while the remaining14.2% was influenced by other variables not mentioned in this study.